Analysis of Regional Planning and Budgeting Consistency in North Central Timor Regency - Mitang, Berno Benigno; Nalle, Frederic Winston (PT Inovasi Pratama Internasional, 2024)
The budget planning and implementation process in North Central Timor Regency (TTU) is faced with significant challenges due to the high level of inconsistency in the budgeting system at each stage. This research aims to explore the relationship between several variables in the North Central Timor Regency. First, an analysis is carried out on the influence of Human Resource capacity (X1) on Good Governance (Y1). Second, the influence of planning quality (X2) on Good Governance (Y1) was examined. Third, audit the impact of Human Resources capacity (X1) on Budgeting Consistency (Y2). Fourth, the impact of planning quality (X2) on Budgeting Consistency (Y2) is analyzed. Fifth, the influence of Human Resource capacity (X1) on Budgeting Consistency (Y2) which is mediated by the Good Governance variable (Y1) is explored. And sixth, we studied the influence of planning quality (X2) on Budgeting Consistency (Y2) with the mediation variable Good Governance (Y1). The research uses quantitative Path Analysis. Samples were taken using a purposive random sampling method, with the criteria being employees in the financial administration field at each regional organization. The research results show that in the first structural equation, HR capacity and planning quality have a direct effect on Good Governance. In the second structural equation, HR capacity, planning quality, and Good Governance influence Budgeting Consistency. However, HR capacity and planning quality cannot be mediated by Good Governance on Budgeting Consistency.